Pastoralne determinanty profilaktyki kryzysu małżeństwa - Wojaczek, Krystian (Studia Pastoralne, 2026)
Title of the article means that the pastoral activity of the Church carries the potential of preventive measures against the crisis of marriage. Actualisation of this potential requires, first of all, adequate definition of marriage crisis as a situation in which the following factors coexist: factors that disrupt marriage, the need for an immediate change in the existing situation and the uncertain outlook for the future of the relationship. A derivative term related to a marriage crisis is the concept of crisis tendencies, which means the occurrence of one or at most two factors creating a marriage crisis. The concept of crisis tendencies is important from the point of view of prevention and pastoral commitment of the Church. This commitment can reverse the said tendency and help the marriage to avoid a crisis. One should point at the three elements of the pastoral commitment of the Church in the marriage crisis prevention. The first is to present spouses a model of marriage as their reciprocal gift of themselves. This model is important because it stems from the fact of their personal being. Secondly, it is necessary to show spouses the so called know how knowledge that are mechanisms of various fields of their married life. Here the Church should take advantage of the achievements of humanities. It is important that the choice of these solutions be integrated into the model. Otherwise instead of marriage prevention one shall face disintegration of marriage. Thirdly, a married couple should be informed each time of from which field a particular content comes from: whether it is the official teaching of the Church or a detailed solution offered by secular science. Synergistic approach is often impossible because of the socio-phenomenological model of the sacred-profane relationship by Durkheim and Eliade. That it why a good knowledge of the Second Vatican Council on the autonomy of the temporal is required.